Androgen receptor expression and its relationship with clinicopathological parameters in an Iranian population with invasive breast carcinoma - Mohammadizadeh, Fereshteh (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Androgen receptor (AR) status and its association with prognosis in Iranian breast cancer population are uncertain. We examined AR expression and its relationship with clinicopathological parameters among Iranian patients with invasive breast carcinoma. MATERIALS AND METHODS: This study was performed on formalin fixed and paraffin embedded tissue specimens with a diagnosis of invasive breast carcinoma archived at two University Hospitals in Isfahan city, Iran. Antibodies were used for evaluation of AR, human epidermal growth factor receptor 2 (HER2), estrogen receptor (ER), and progesterone receptor (PR). Other data were gathered from patients’ documents. RESULTS: A total of 70 cases were evaluated including 55 (78.6%) ductal, 9 (12.9%) lobular, 2 (2.9%) medullary, and 4 (5.7%) mucinous carcinomas. Overall, 48.6%, 42.9%, 64.3%, and 57.1% of the samples were positive for ER, PR, AR, and HER2, respectively. Thirty three (47.1%) cases were ER(−) PR(−) and 17.1% were triple negative. AR + cases were younger and more frequently positive for ER and showed less frequently tumor size of > 2 cm. Although tumor grade and stage were relatively higher among AR(−) cases compared to AR(+) ones, the difference between the two groups was not statistically significant. CONCLUSIONS: AR expression was found to be frequently present in breast carcinoma in the studied population. Since half of the ER negative and half of the triple negative tumors were found to be AR positive, AR positive cases may benefit from alternative endocrine therapeutic strategies other than the conventional endocrine-targeted medications.